Fabrication Scheduling of Electrical House of FPSO using Dependency Structure Matrix - Ahmad, Norhaziyah Afiqah Binti; Effendy, Moh Hafidz; Koto, Jaswar (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
Electric House is a complete power plant system that supplies the electrical distribution network to site. Installation this power plant system have used in the world wide especially in industrial, utilities, renewable energy, outdoor switchgear and moveable substation. As we can see, in offshore industries application, Electrical House can be installed in Floating Production and Storage Offloading (FPSO). Since, engineering work is procedural and repeatable, complexity process will repeat again and again. Thus, problem happens stemming when complex processes which involves interdependent (feedback and iteration) in designing and fabricating process that affect the schedule of the project. Project management tools such as CPM, PERT and Gantt widely used to scheduling application do not address complexity of the interdependency and feedback iteration. In this research discusses scheduling of FPSO E-House module Fabrication Model using Dependency Structure Matrix (DSM) method in order to address the complexity. Partitioning DSM process which minimize the amount of iteration (iteration) within the process. As a result, reducing probability of iteration will affect to the time reduction to complete the project.